2015
DOI: 10.1155/2015/676212
|View full text |Cite
|
Sign up to set email alerts
|

The Verbal Rating Scale Is Reliable for Assessment of Postoperative Pain in Hip Fracture Patients

Abstract: Background. Hip fracture patients represent a challenge to pain rating due to the high prevalence of cognitive impairment. Methods. Patients prospectively rated pain on the VRS. Furthermore, patients described the changes in pain after raising their leg, with one of five descriptors. Agreement between paired measures on the VRS at rest and by passive straight leg raise with a one-minute interval between ratings at rest and three-minute interval for straight leg raise was expressed by kappa coefficients. Reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 31 publications
0
30
0
2
Order By: Relevance
“…Several previous articles suggested the use of unidimensional scales to measure acute pain [ 5 6 20 21 22 23 24 25 ], caused by trauma, surgery, childbirth, or an acute medical disease. Previous OMFS articles mostly used the VAS for pain assessment in acute pain.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous articles suggested the use of unidimensional scales to measure acute pain [ 5 6 20 21 22 23 24 25 ], caused by trauma, surgery, childbirth, or an acute medical disease. Previous OMFS articles mostly used the VAS for pain assessment in acute pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of spinal anesthesia (SA) for surgery constitute a longstanding subject of debate, it has been reported that regional anesthesia (RA) protocols like SA reduce the risks of pulmonary complications, deep vein thrombosis, and mortality [4,5]. Spinal anesthesia is primarily applied in elderly patients versus general anesthesia (GA) [6] in our institution.…”
Section: Introductionmentioning
confidence: 99%
“…Pain was rated using the 5-point Verbal Rating Scale which we have found reliable for assessment of pain after hip fracture in a previous study [ 24 ]. Cognitive status was assessed by admission using the six-item SOMC which is validated to test for cognitive impairment [ 5 , 25 ] since our protocol prescribed a certain cognitive level to ensure that all subjects were able to administer analgesics on demand and to evaluate pain reliably.…”
Section: Discussionmentioning
confidence: 99%